2018
DOI: 10.1210/jc.2018-00674
|View full text |Cite|
|
Sign up to set email alerts
|

Advanced Glycation End Products and esRAGE Are Associated With Bone Turnover and Incidence of Hip Fracture in Older Men

Abstract: Glycemia associates positively with CML and reciprocally with esRAGE in older men. Circulating esRAGE modulates bone turnover in older men, whereas CML predicts incidence of hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
3
21
3
Order By: Relevance
“…Higher serum CML, a frequently studied AGE, was related to higher risk of incident hip fractures in two longitudinal cohort-studies in elderly subjects. (21,41) In one of these studies, in 3384 community-dwelling men aged 70 to 89 years, a nonlinear relation was found of CML with incident hip fractures, which is similar to our findings of a nonlinear relationship of SAF with prevalent hip fractures. (41) Compared to the other two cohorts with a longitudinal design, our subjects were relatively younger with fewer prevalent hip fractures, but we still observed the same trend ( Table 5).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Higher serum CML, a frequently studied AGE, was related to higher risk of incident hip fractures in two longitudinal cohort-studies in elderly subjects. (21,41) In one of these studies, in 3384 community-dwelling men aged 70 to 89 years, a nonlinear relation was found of CML with incident hip fractures, which is similar to our findings of a nonlinear relationship of SAF with prevalent hip fractures. (41) Compared to the other two cohorts with a longitudinal design, our subjects were relatively younger with fewer prevalent hip fractures, but we still observed the same trend ( Table 5).…”
Section: Discussionsupporting
confidence: 89%
“…(21,41) In one of these studies, in 3384 community-dwelling men aged 70 to 89 years, a nonlinear relation was found of CML with incident hip fractures, which is similar to our findings of a nonlinear relationship of SAF with prevalent hip fractures. (41) Compared to the other two cohorts with a longitudinal design, our subjects were relatively younger with fewer prevalent hip fractures, but we still observed the same trend ( Table 5). Urinary pentosidine was associated with incident long-bone and vertebral fractures in a linear fashion in Japanese subjects (n = 765), but no association was found in French (n = 396) postmenopausal women.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with this possibility, low serum esRAGE levels is a risk factor for vertebral fractures [86]. Additionally, low serum sRAGE and S100A12 levels in juvenile idiopathic arthritis correlated with increased disease activity [87].…”
Section: Rage As a Biomarker For Bone Disease/osteoporosismentioning
confidence: 79%
“…There are differences in the affinity of different AGEs for RAGE and its activation. Whether this underpins the variable relationship between different AGEs and fracture risk remains to be elucidated [19,24]. Although SAF predicts traditional diabetic complications independently of HbA 1c [12], whether it can help stratify for fracture risk in people with diabetes is unclear.…”
Section: Discussionmentioning
confidence: 99%